Assessment of genetic variability for N2 fixation between and with provenance of Leucaena leucocephala and Acacia albida estimated by 15N labelling techniques - Sanginga, N.; Bowen, G.D.; Danso, S.K.A. (1990)
Nitrogen fixed in 13 provenances of Acacia albida and 11 isolines of Leucaena leucocephala inoculated with effective Rhizobium strains was measured by 15N techniques and the total N difference method. In the test soil, on the average, L. leucocephala derived about 65% of its total N from atmospheric N2 fixation compared to about 20% by A. albida. Significant differences in the percentage of N derived from atmospheric N2 (% Ndfa) occurred, between provenances or isolines within species. The % Ndfa ranged from 37 to 74% within L. leucocephala and from 6 to 37 within A. albida ; (equivalent to 20-50 mg N plant-1 and 4-37 mg N plant-1 for the two species over three months, respectively) and was correlated with the nodule mass (r = 0.91). The time course of N2 fixation of three selected provenances (low, intermediate and good fixers) was followed at 12 weekly intervals over a 36 week period. The % Ndfa of all provenances and isolines increased with time; and except for one of the L. leucocephala provenances, % Ndfa was similar within species at the 36 weeks harvest. There was a significant correlation between % Ndfa and the amount of N2 fixed (r = 0.96). Significant interactions occurred between provenances and N treatments and often growth of uninoculated but N fertilized plants was less variable than for inoculated unfertilized plants.